2011
DOI: 10.1021/la104981s
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine−Melanin Film Deposition Depends on the Used Oxidant and Buffer Solution

Abstract: The deposition of "polydopamine" films, from an aqueous solution containing dopamine or other catecholamines, constitutes a new and versatile way to functionalize solid-liquid interfaces. Indeed such films can be deposited on almost all kinds of materials. Their deposition kinetics does not depend markedly on the surface chemistry of the substrate, and the films can reach thickness of a few tens of nanometers in a single reaction step. Up to now, even if a lot is known about the oxidation mechanism of dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
447
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 506 publications
(469 citation statements)
references
References 24 publications
19
447
1
2
Order By: Relevance
“…Of the highest interest is that the deposition of polydopamine occurs at a pH of about 4 when ammonium persulfate is the oxidant. The same finding holds true when copper (II) sulfate is the oxidant [52]. These findings show that some fundamental investigations about the oxidation mechanism of dopamine into dopamine quinone, which is known to be a pH-dependent equilibrium, are necessary (Scheme 2).…”
Section: Mechanism Of Polydopamine Film Formationsupporting
confidence: 66%
“…Of the highest interest is that the deposition of polydopamine occurs at a pH of about 4 when ammonium persulfate is the oxidant. The same finding holds true when copper (II) sulfate is the oxidant [52]. These findings show that some fundamental investigations about the oxidation mechanism of dopamine into dopamine quinone, which is known to be a pH-dependent equilibrium, are necessary (Scheme 2).…”
Section: Mechanism Of Polydopamine Film Formationsupporting
confidence: 66%
“…17 Therefore, the copper chelated on the PDA deposited membrane surfaces was mostly in the form of Cu 2+ and Cu + , and no metallic copper was found, which is consistent with the previous study. 18 To understand the role of Cu 2+ in the polymerization of DOPA solution, UV-VIS was used to monitor the formation of PDA having a characteristic absorbance peak at 420 nm. 16 When DOPA solution was acidic at pH 4.5, as shown in Figure S5, there was no absorbance detected at 420 nm and no color change observed in air with the absence of Cu 2+ , which has been reported that DOPA could not selfpolymerize at acidic condition.…”
Section: Zongyao Zhou 12mentioning
confidence: 99%
“…This suggests that the polydopamine deposited in the (PAH-MMT) 10 film is much important than the *35 nm thick layer grown on quartz in these conditions [34]. Even if the reaction time of 14 h between the film and the oxygenated dopamine solution may not be sufficient to fill the film homogenously with polydopamine through its whole thickness, it was nevertheless sufficient to significantly modify the properties of the (PAH-MMT) n films, as will be shown below.…”
Section: Resultsmentioning
confidence: 99%